Antimicrobial Dilution Susceptibility Testing of Erysipelothrix rhusiopathiae According to CLSI Document VET06 Reveals High Resistance against Penicillin G, Erythromycin and Enrofloxacin - Claudia Hess; Ivana Bilic; Delfina Jandreski-Cvetkovic; Michael Hess (Poultry, 2023)
Erysipelas is a re-emerging disease in different poultry species. Antibiotic treatment is crucial to combat outbreaks in poultry flocks, but only very limited data on susceptibility are available. Recently, the Clinical and Laboratory Standard Institute established standardized guidelines and minimal inhibitory concentration breakpoints for E. rhusiopathiae when using the broth microdilution method. In the present investigation, these guidelines were applied to evaluate the antimicrobial susceptibility of 30 E. rhusiopathiae isolates derived from field outbreaks in poultry flocks towards penicillins, macrolides, lincosamides and fluoroquinolones. All isolates were identified by MALDI-TOF MS. The majority of isolates belonged to two serovars, 1b and 5. More than 40% of the isolates proved resistant to penicillin G, with values ranging from 0.25 to 8 µg/mL. Furthermore, the majority of isolates were found resistant to erythromycin (76.7%; MIC 2–4 µg/mL) and enrofloxacin (60.0%; MIC ≥ 2 µg/mL), altogether limiting treatment options. In contrast, most of the isolates proved susceptible to ampicillin and ceftiofur with MICs ≤ 0.25 µg/mL and ≤2 µg/mL, respectively. A great variety of antimicrobial resistance patterns was found, and multidrug resistance was detected in one-third of the isolates. The presented data are helpful to raise awareness for the antimicrobial resistance of a zoonotic pathogen in context of the One Health concept.